The Internal Work Environment and Job Alienation: The Case of Faculty Members - Bougherza, Rédha; Azieb, Samia; Abdo Noufal, Zezit M.; Mallek, Mohamed; Abderrahmane, Yasser; Brachene, Imed Eddine; Menighed, Ahmed (Emerging Science Journal, 2024)
The objective of this study is to examine the nature of the relationship between the internal work environment including its all-encompassing dimensions (organizational structure, participation in decision-making, incentives) and job alienation in Higher education institutions through focusing on faculty members at Jijel University in Algeria. That being the case, the study aims to fill a research gap by investigating the underexplored relationship between the Internal Work Environment and Job Alienation, hence while there is ample literature on work alienation, studies specifically focusing on work alienation within higher education institutions through the prism of internal work environment are notably scarce. The study utilized a descriptive approach, employing a survey sampling method to collect data from the target population with a specifically designed questionnaire for this purpose. The questionnaire consisting of 60 items was administered to a randomly selected sample of 167 faculty members at Jijel University. The collected data were analyzed through the Statistical Package for Social Sciences (SPSS), version 22. The study's findings illustrate that faculty members perceive their work environment as inadequate for carrying out their activities, coupled with a notably high level of job alienation. Additionally, the research underscores a significant correlation between the internal work environment, encompassing its various dimensions, and the prevalence of job alienation among faculty members at Jijel University. Doi: 10.28991/ESJ-2024-SIED1-07 Full Text: PDF